2016
DOI: 10.2337/diaspect.29.2.71
|View full text |Cite
|
Sign up to set email alerts
|

Macronutrient Composition or Social Determinants? Impact on Infant Outcomes With Gestational Diabetes Mellitus

Abstract: The purpose of this study was to examine, through a randomized, controlled trial, the effects of a maternal carbohydrate-restricted diet on maternal and infant outcomes in gestational diabetes mellitus (GDM). Women diagnosed with GDM were randomly allocated into one of two groups: an intervention group that was placed on a lower-carbohydrate diet (35–40% of total calories) or a control group that was placed on the usual pregnancy diet (50–55% carbohydrate). A convenience sample of participants diagnosed with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Sample sizes ranged from 45 ( 35 ) to 1,030 ( 19 ) newborns. 13 studies ( 20 , 21 , 24 , 25 , 35 42 , 44 ) had a sample size of fewer than 300 newborns. Five studies were conducted in China ( 21 , 22 , 24 , 36 , 43 ), four in Iran ( 25 , 35 , 38 , 44 ), two each in the United States ( 26 , 42 ) and Australia ( 19 , 41 ), and one each in the United Arab Emirates ( 20 ), Canada ( 37 ), Egypt ( 39 ), the United Kingdom ( 40 ), and Singapore ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample sizes ranged from 45 ( 35 ) to 1,030 ( 19 ) newborns. 13 studies ( 20 , 21 , 24 , 25 , 35 42 , 44 ) had a sample size of fewer than 300 newborns. Five studies were conducted in China ( 21 , 22 , 24 , 36 , 43 ), four in Iran ( 25 , 35 , 38 , 44 ), two each in the United States ( 26 , 42 ) and Australia ( 19 , 41 ), and one each in the United Arab Emirates ( 20 ), Canada ( 37 ), Egypt ( 39 ), the United Kingdom ( 40 ), and Singapore ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the control group, the mean maternal age ranged from 26.20 ± 3.10 ( 44 ) to 32.20 ± 4.40 ( 23 ) years. Studies were initiated in the first ( n = 3) ( 36 , 39 , 43 ), second ( n = 6) ( 21 , 23 , 25 , 35 , 38 , 40 ), and third ( n = 6) ( 19 , 22 , 24 , 26 , 41 , 42 ) trimesters, while three studies ( 20 , 37 , 44 ) were unspecified. Specific gestational age at trial entry was reported in 13 studies ( 19 , 21 24 , 26 , 35 , 36 , 38 , 40 43 ), with a mean age ranging from 10.00 ± 0.32 ( 36 ) to 30.46 ± 4.71 ( 24 ) weeks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Trout et al ( 17 ), in an article published in this issue of Diabetes Spectrum (p. 71), compared a low-carbohydrate diet (40% carbohydrate, 40% fat, and 15% protein) to a high-carbohydrate diet. However, the primary outcome of lower 2-hour postprandial blood glucose was not achieved.…”
mentioning
confidence: 99%